2013 International Conference on Parallel and Distributed Computing, Applications and Technologies 2013
DOI: 10.1109/pdcat.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of Wireless Ad Hoc Networks: Impacts of Antenna Models

Abstract: Abstract-This paper concerns the impact of various antenna models on the network connectivity of wireless ad hoc networks. Existing antenna models have their pros and cons in the accuracy reflecting realistic antennas and the computational complexity. We therefore propose a new directional antenna model called Approx-real to balance the accuracy against the complexity. We then run extensive simulations to compare the existing models and the Approx-real model in terms of the network connectivity. The study resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our previous paper [ 43 ], we conducted a preliminary study on the network connectivity in terms of the path probability. However, this paper is significantly different from our previous work [ 43 ] in the following aspects: (i) we investigate the network connectivity within a general theoretical framework, in which we consider the channel randomness and various directional antenna models; (ii) we analyze both the local connectivity (in Section 5 ) and the overall connectivity (in Section 6 ); (iii) we conduct extensive simulations to verify the effectiveness and the accuracy of our analytical model with consideration of both the local connectivity and the overall connectivity.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous paper [ 43 ], we conducted a preliminary study on the network connectivity in terms of the path probability. However, this paper is significantly different from our previous work [ 43 ] in the following aspects: (i) we investigate the network connectivity within a general theoretical framework, in which we consider the channel randomness and various directional antenna models; (ii) we analyze both the local connectivity (in Section 5 ) and the overall connectivity (in Section 6 ); (iii) we conduct extensive simulations to verify the effectiveness and the accuracy of our analytical model with consideration of both the local connectivity and the overall connectivity.…”
Section: Related Workmentioning
confidence: 99%
“…In this model, the sector with angle represents the main lobe of the antenna, which has the maximum gain denoted by (where is also called the antenna beamwidth), and the circular part represents the side-lobes and back-lobes with lower antenna gain denoted by . In particular, when and are given [53,54], we can calculate as follows:…”
Section: Channel Modelmentioning
confidence: 99%
“…It was shown that the presence of fading could result in an improvement of overall connectivity. The connectivity of wireless AHNs where nodes are equipped with directional antennas was presented in [7,8,9,10]. In [7], the study was performed by using accurate, analytical antenna models, i.e., Uniform Linear Array (ULA) antenna and Uniform Circular Array (UCA) antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-hop connectivity of AHNs with antenna model given by cardioid function was mathematically investigated in [9]. Comparisons of the influences of various antenna models on the network connectivity of wireless AHNs were shown in [10].…”
Section: Introductionmentioning
confidence: 99%